2012
DOI: 10.1590/s0482-50042012000300013
|View full text |Cite
|
Sign up to set email alerts
|

Mielopatia torácica por calcificação do ligamento amarelo cursando com hiperproteinorraquia e resposta à corticoterapia: relato de caso

Abstract: Calcifi cation and ossifi cation of the ligamentum fl avum or of the posterior longitudinal ligament are causes of compressive myelopathy, more frequent in the lower thoracic levels, and extremely rare in Western populations. Surgical decompression is the only therapy, but the disease is usually progressive, and its recurrence after surgery is common. Infl ammatory mediators might play a role in the progression of compressive myelopathy, but, to our knowledge, the therapeutic approach involving anti-infl ammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Compressive myelopathy can occur in OLF and OPLL [7] and contemporary occurrence of OPLL and OLF and DISH has also been reported [2]. DISH is a common spinal disorder involving about 12% of the middleaged men [8] but it occurs more frequently in diabetic patients and its symptoms present in 25% of diabetic patients [9] A and B show Large OPLL at the level of C2 and C3, respectively with spinal canal stenosis; C. Ossification of anterior longitudinal ligament at the level of C2 to C7 and OPLL at the level of C2-C3 and C6-C7 and T1-T2 and OLF of C2-C3 and T1-T2…”
Section: Discussionmentioning
confidence: 99%
“…Compressive myelopathy can occur in OLF and OPLL [7] and contemporary occurrence of OPLL and OLF and DISH has also been reported [2]. DISH is a common spinal disorder involving about 12% of the middleaged men [8] but it occurs more frequently in diabetic patients and its symptoms present in 25% of diabetic patients [9] A and B show Large OPLL at the level of C2 and C3, respectively with spinal canal stenosis; C. Ossification of anterior longitudinal ligament at the level of C2 to C7 and OPLL at the level of C2-C3 and C6-C7 and T1-T2 and OLF of C2-C3 and T1-T2…”
Section: Discussionmentioning
confidence: 99%
“…The latter is responsible for the reduced mobility of the thoracic spine compared to the cervical spine, which is thought to contribute to the lower prevalence of degenerative spinal myelopathy at the thoracic compared to the cervical level. 1,2 Myelopathy from thoracic spondylotic myelopathy, and other forms of thoracic spine degeneration, including ossification of the posterior longitudinal ligament (OPLL), 3 ossification of the ligamentum flavum (OLF), [4][5][6] calcification of ligaments, 5,7 hypertrophy of ligaments, 5 degenerative disc disease (DDD), thoracic osteoarthritis, intervertebral disc herniation (with the exception of acute herniation) 8,9 and posterior osteophytes 10,11 (Figure 1) share similarities in presentation and management. They trigger an uncommon, but disabling form of 'slow motion' spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…Myelopathy from thoracic spondylotic myelopathy, and other forms of thoracic spine degeneration, including ossification of the posterior longitudinal ligament (OPLL), 3 ossification of the ligamentum flavum (OLF), 4-6 calcification of ligaments, 5,7 hypertrophy of ligaments, 5 degenerative disc disease (DDD), thoracic osteoarthritis, intervertebral disc herniation (with the exception of acute herniation) 8,9 and posterior osteophytes 10,11 (Figure 1) share similarities in presentation and management. They trigger an uncommon, but disabling form of ‘slow motion’ spinal cord injury.
Figure 1.A sagittal view of the thoracic spine demonstrates several pathologies that can cause DTM, including spondylosis, degenerative disc disease, and ossification of the posterior longitudinal ligament.
…”
Section: Introductionmentioning
confidence: 99%
“…Ossification of the ligamentum flavum (OLF) is an uncommon cause for thoracic myelopathy which demands surgical treatment. This condition usually is described in Far East countries, fairly common in Japanese people 1 , even though rare in Western countries [2][3][4][5] . Two cases were reported in Brazil 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…This condition usually is described in Far East countries, fairly common in Japanese people 1 , even though rare in Western countries [2][3][4][5] . Two cases were reported in Brazil 4,5 . Polgar was the first to describe OLF, in 1929 6 , and Yamaguchi et al 7 , in 1960, reported the first case of OLF causing thoracic myelopathy.…”
Section: Introductionmentioning
confidence: 99%